Induction of Disseminated Intravascular Coagulation in the Factor XII-deficient Fowl - Skjørten, Fredrik; Evensen, Stein A. (Thrombosis and Haemostasis, 1973)
Birds are naturally deficient in the coagulation factors responsible for the contact activation reactions in mammalian plasma. In the present study, fowl lungs were examined for evidence of disseminated intravascular coagulation (DIC) 5 min or 4 hours after injection of either Liquoid or bacterial endotoxin. These substances are potent initiators of DIC in mammals, and activation of factor XII is believed to be essential for their triggering effect.Liquoid injection produced intravascular deposits with the light microscopical staining properties of fibrin. However these deposits had a purely granular ultra-structure; their formation was not prevented by adequate anticoagulation, and there was no concomitant thrombocyte aggregation. It is suggested that the deposits represent precipitates of plasma proteins, including fibrinogen.Endotoxin failed to produce clinical reactions, intravascular deposits or thrombocyte aggregates. In contrast, animals injected with homologous tissue thromboplastin died, and fibrillar material with the ultrastructural appearance of fibrin, as well as thrombocyte aggregates were found in small pulmonary vessels. These effects were completely prevented by anticoagulation.We conclude that both Liquoid and endotoxin failed to trigger DIC in the factor XII-deficient fowl, suggesting that these substances depend on the contact activation reactions for the generation of thrombin.